2022
DOI: 10.1016/j.techsoc.2022.101912
|View full text |Cite
|
Sign up to set email alerts
|

A COVID-19 disruption: The great acceleration of digitally planned and transformed behaviors in Thailand

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has reshaped human behaviors and switched communication systems from face-to-face to digital communication technologies. This study aimed to examine how digital transformation practices affect human behavioral change digitally, and how perceived COVID-19 severity affects digital transformation practices and behavioral decisions. We use the traditional theory of planned behavior (TPB) to determine new behavioral roles in the digital era, namely digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 99 publications
0
35
0
Order By: Relevance
“…For example, group discussion, cultural understanding or social interaction are the types of activities that indicate the presence of little or no technological devices. However, since the Covid pandemic appeared, these activities can hardly be maintained without the support of technology due to social distancing [7], [13], [15], [16] It is knowledgeable that digital transformation has been quietly happening for many years and that Covid-19 is the agent that makes the process of digital transformation happen faster [17], [18]. While some developed countries have taken advantage of their strengths in resources, infrastructure and technology to pioneer in this field, others are struggling to find their way [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, group discussion, cultural understanding or social interaction are the types of activities that indicate the presence of little or no technological devices. However, since the Covid pandemic appeared, these activities can hardly be maintained without the support of technology due to social distancing [7], [13], [15], [16] It is knowledgeable that digital transformation has been quietly happening for many years and that Covid-19 is the agent that makes the process of digital transformation happen faster [17], [18]. While some developed countries have taken advantage of their strengths in resources, infrastructure and technology to pioneer in this field, others are struggling to find their way [19].…”
Section: Introductionmentioning
confidence: 99%
“…Esports live consumption and the theory of planned behavior Exploring how identified factors impact individual decision-making processes is essential to understanding consumers (Zhao and Gao, 2022). The TPB is one of the most broadly used theories in human decisions and behaviors research (Giachino et al, 2023;Han et al, 2020;Kumari et al, 2022;Srisathan and Naruetharadhol, 2022). Ajzen (1991) proposed the TPB to explain human actions based on behavioral, normative and control beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students understand better when the material is presented using writing and pictures when compared to oral presentation only [3]. Meanwhile provides compelling evidence: people are struggling during the pandemic to change digital behavior, such as cultivating digital attitudes, promoting digital social norms, increasing perceptions of digital behavior control, and improving digital behavioral decisions [4]. Both studies have indicated that the pandemic has indeed accelerated digital disruption.…”
Section: Introductionmentioning
confidence: 99%